Prevalence of HIV infection and syphilis among adolescents in a juvenile justice system - Miranda, Angélica E.; Zago, Adriana M. (Brazilian Journal of Sexually Transmitted Diseases, 2001)
Background: To determine the seroprevalence of HIV infection and syphilis and identify risk factors for these infections among adolescents in a court stay juvenile justice system in Vitoria, Brazil. Methods: Cross-sectional study was conducted from March to June 1999. They were interviewed using a structured questionnaire and a blood sample was collected for testing HIV and syphilis. Results: A total of 103 adolescents were included, 92.2% male and 7.8% female. The prevalence rates were: HIV infection 4.9% (IC95% 1.0%-9.0%) and syphilis 7.8% (IC 95% 2.6%-12.8). The mean age was 16.3 years old (SD1.24) and mean education was 4.6 years of schooling (SD2.4). The mean time in prison was 2.1 days (SD37.63), ranging from 1 day to 5 months; previous imprisonment were reported by 34%. The risk factors accessed were: 52.4% never used condoms; 28.9% reported history of STDs and 50.5% used any illicit drug (cannabis 39.8%; glue 13.6%; snuffing cocaine 26.2%; crack 13.6% and injecting cocaine 10.7%). Injecting drug abuse were statistical associated to HIV infection (OR=27; 95%IC: 2..5-219.18), and syphilis (OR=8.7; 95% IC:1.5-50.83). Conclusion: Adolescents who are under the jurisdiction of the juvenile justice system in Vitoria are at significant risk for HIV infection. The rates identified in this study confirm that there is a problem to be controlled and show the urgent need for prevention programs and counseling to this population.